Bulgaria Report on the Observance of Standards and Codes : Insolvency and Creditor-Debtor Regimes - World Bank Group (World Bank, Washington, DC, 2017)
The World Bank Group assessed the insolvency and creditor/debtor regimes (‘ICR’) of Bulgaria pursuant to the joint IMF/World Bank initiative on the observance of standards and codes (‘ROSC’). The assessment has been undertaken on the basis of the ICR Standard. The conclusions in this assessment are based on a review of the legislation, and other regulations and procedures relevant to bankruptcy, restructuring, the creation and enforcement of pledges and other security interests over immovable and movable property, and debt enforcement. The Bulgarian legal framework governing creditor/debtor relationships provides several means for protecting credit and minimizing the risks of non-performance and default. However, the laws and institutions governing security rights over both immovable and movable assets need improvement. The bankruptcy legislation is rather comprehensive but in practice insolvency proceedings are not working effectively. This report tries to contribute to the authorities’ efforts aimed at continuing and further improving the laws and institutions related to credit relationships.